ANALYSIS OF FACTORS AFFECTING E-COMMERCE ADOPTION AND THEIR EFFECT ON MSME PERFORMANCE - Primadona (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2019)
E-Commerce is often referred to as one of the drivers of economic growth in Indonesia. The huge potential of e-commerce cannot be separated from the development of internet users in Indonesia. In 2015, internet users in Indonesia reached 93.4 million people, an increase quite rapidly when compared to 88.1 million people in 2014. The potential for e-commerce can be seen from the figure that 77% of internet use is used to find product information and shop online, online shop customers who reach 8.7 million people, and the transaction value is predicted to reach US$ 4.89 billion in 2016. Small, Micro and Medium Enterprises (MSMEs) in Indonesia have an important role in the national economy. MSMEs are required to make changes and innovations to increase competitiveness, one of which is by utilizing e-commerce. This research was conducted using a quantitative approach. The research data were obtained from various MSMEs in Central Java. The results of this study indicate that technological factors and individual factors partially have a positive and significant effect on e-commerce adoption. On the other hand, organizational factors partially have a negative and insignificant effect on e-commerce adoption and environmental factors partially have positive and insignificant effects on e-commerce adoption in MSMEs.